2016
DOI: 10.1155/2016/3672416
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystostomy as Bridge to Surgery and as Definitive Treatment or Acute Cholecystectomy in Patients with Acute Cholecystitis

Abstract: Purpose. Percutaneous cholecystostomy (PC) has increasingly been used as bridge to surgery as well as sole treatment for patients with acute cholecystitis (AC). The aim of the study was to assess the outcome after PC compared to acute cholecystectomy in patients with AC. Methods. A review of medical records was performed on all patients residing in Stockholm County treated for AC in the years 2003 and 2008. Results. In 2003 and 2008 altogether 799 and 833 patients were admitted for AC. The number of patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
1
19
1
7
Order By: Relevance
“…13 Our data showed that in such high-risk cases that even when a PC drain was deployed during the first admission, that the need for elective surgery can be selective 31 and that PC drainage can act as definitive management. 32,33 Although the treatment options are competitive, these patient groups are not, however, strictly comparable.…”
Section: Discussionmentioning
confidence: 77%
“…13 Our data showed that in such high-risk cases that even when a PC drain was deployed during the first admission, that the need for elective surgery can be selective 31 and that PC drainage can act as definitive management. 32,33 Although the treatment options are competitive, these patient groups are not, however, strictly comparable.…”
Section: Discussionmentioning
confidence: 77%
“…admitted in 2003, and 850 in 2008. Multivariate regression analysis was performed with adjustments for age, gender, degree of cholecystitis and Charlson comorbidity index (33). Notably, although patients treated with cholecystectomy as a bridge to elective surgery, were older with a predominance of females, the complications reported in the "bridge to surgery" group were entirely con ned to the subsequent nal gallbladder operation, con rming the Authors' conclusion that PC is a safe option in high risk patients with ACC.…”
Section: Discussionmentioning
confidence: 80%
“…[12] In another study, performed by Popowicz et al, which compared 71 cases from 2 different time periods (2003 and 2008), recurrence rate of AC was reported to be 28%. [13] Also, Yeo et al reported readmission rate of 6.8% in their study consisting of 103 cases. LC was performed in 81% and conversion rate was 15% in that study.…”
Section: Discussionmentioning
confidence: 93%